2018
DOI: 10.1038/s41388-018-0608-2
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear MET requires ARF and is inhibited by carbon nanodots through binding to phospho-tyrosine in prostate cancer

Abstract: Nuclear receptor tyrosine kinases (nRTKs) are aberrantly upregulated in many types of cancers, but the regulation of nRTK remains unclear. We previously showed androgen deprivation therapy (ADT) induces nMET in castration resistant prostate cancer (CRPC) specimens. Through gene expression microarray profiles reanalysis, we identified that nMET signaling requires ARF in CRPC in vivo Arf deficiency in Pten/Trp53 conditional knockout mouse model. Accordingly, aberrant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 51 publications
3
15
0
Order By: Relevance
“…In summary, we systematically analyzed the C‐dots‐mediated nanozyme, DNA damage, DNA repair, and cell death in both cancer cells and bacteria with novel discovery that the C‐dots induce pH‐mediated nanozyme inhibition, photo‐induced nanozyme activity, destroy of BER‐mediated DNA repair, and kinase‐mediated cell proliferation, which are consistent with our previous hypothesis of MET kinase synergistic DNA damage targeted pathway …”
Section: Resultssupporting
confidence: 84%
“…In summary, we systematically analyzed the C‐dots‐mediated nanozyme, DNA damage, DNA repair, and cell death in both cancer cells and bacteria with novel discovery that the C‐dots induce pH‐mediated nanozyme inhibition, photo‐induced nanozyme activity, destroy of BER‐mediated DNA repair, and kinase‐mediated cell proliferation, which are consistent with our previous hypothesis of MET kinase synergistic DNA damage targeted pathway …”
Section: Resultssupporting
confidence: 84%
“…In our previous research, carbon nanodots developed from food or herbal food were shown to exhibit PL activity, and their binding to the phosphate group on the protein was identied by molecular spectroscopy and supported by quantum mechanical calculations. 30 Phosphatases, especially tyrosine phosphatase (PTP), have been recognized to suppress cancer cell growth and other oncogenic characteristics by intervening in cell signaling, wherein phosphatase most likely dysregulates the phosphorylation-dephosphorylation balance to disrupt cancer cell signaling. [31][32][33] As a continuation of our previous work, we aim to correlate the nanostructures or their assemblies formed through RP processing with the enzyme-like activities demonstrated in the nal products by means of FT-IR spectroscopy and enzymatic tests combined with quantum mechanical calculations.…”
Section: Introductionmentioning
confidence: 99%
“…(3) Hydrolase of ALP One example of a class of hydrolase is alkaline phosphatase (ALP) (EC 3.1.3.1) which functions as removing of phosphorylation and some types of nanoparticles have been reported to have intrinsic phosphatase activity [11,16]. Recently we discovered natural product derived nanodots or nanoflowers which have the ability to dephosphorylate substrates as ALP-like nanozymes in addition to the chemical synthesis of nanozyme [9,11,17].…”
Section: ) Transferases Of Hexokinase and Glutathione S-transferase (Gst)mentioning
confidence: 99%